Multi-drug resistant gram negative bacteria colonization and infection in burned children: Lessons learned from a 20-year experience - Robert Sheridan; Joan Weber; Philip Chang; John Schulz; Jeremy Goverman; Jonathan Friedstat; Carlos Duran; John Benjamin; Mark Pasternack (Elsevier, 2018)
Objectives: Our objective is to highlight the growing problem of multi-drug resistant gram negative bacterial (MDRGNB) species in burn units and demonstrate strategies for successful management. Methods: Using a concurrent data collection, a 20-year experience with MDRGNB in a pediatric burn unit was reviewed. Results: 220 (6.5%) of 3,359 children admitted for management of acute burns or open wounds had MDRGNB recovered. The children had an average age of 8.8 ± 0.3 years and average burn size of 42.9 ± 22.8 percent. The incidence of MDRGNB increased over the 20 years of the study from 2.5% of admissions in the first decade to 8.6% in the second. 90% (198) were found colonized with MDRGNB on admission on transfer from other facilities. MDRGNB sepsis (blood recovery) occurred in 80 (36.4%), MDRGNB invasive wound infection in 46 (20.9%), MDRGNB pneumonia in 19 (8.6%), and MDRGNB UTI in 46 (20.9%) of the children. There were 14 (6.4%) fatalities, the cause of death being MDRGNB sepsis in all 14 children. However the large majority of the children 206 (93.6%) survived despite their MDRGNB infection. Conclusions: MDRGNB may be transferred into burn units during transfers of patients with complex wounds and can be the cause of life threatening infections. The number of children arriving with MDRGNB organisms has steadily increased over time. MDRGNB infected patients can be successfully managed with wound excision and closure supported by topical mafenide acetate and administration of the limited antibiotics to which the organisms are sensitive, particularly Colistin. Strict infection control practices will limit cross infection with these difficult organisms. Keywords: Burns, Children, Resistant bacteria, Sepsis, Drug resistance, Multiple drug resistance